(untitled) (BIRDEM Medical Journal, 2023)
Background: Hysterectomy is by far the commonest major gynaecological procedure done for several indications. A thorough history, careful physical examination and some simple investigations are all that is needed to establish the diagnosis justifying the need for hysterectomy in most of the cases. But even with the advent of modern technologies, a good proportion of patients are misdiagnosed preoperatively which is evident after histopathological confirmation. This study aimed to evaluate the clinical diagnoses which ultimately lead to hysterectomy and to find out to what extent they are consistent with the final diagnoses after confirmation by histopathological examination. Methods: This observational study was carried out in the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January to June 2018. Total 100 patients, irrespective of age and parity, were included whose total abdominal hysterectomy was planned. History, clinical findings, investigation reports and histopathological reports were recorded. Then clinical and histopathological diagnoses were tabulated and expressed as proportion. Results: The incidence of total abdominal hysterectomy was highest (49%) among the age group of 41-50 years. Average age of the study subjects was 45.3 years. Majority of the hysterectomies were done for fibroid uterus (48%) and abnormal uterine bleeding due to ovulatory dysfunction (AUB-O) (16%). Histopathology confirmed fibroid or leiomyoma in 39% cases versus clinical diagnosis of 48% and 18% of the specimens revealed no organic lesion on histopathology. Conclusion: Though not remarkable, still a certain proportion of clinical diagnoses differ with histopathological findings in patients undergoing hysterectomy even in tertiary level. BIRDEM Med J 2023; 13(1): 27-33